2011
DOI: 10.1007/s11666-011-9677-2
|View full text |Cite
|
Sign up to set email alerts
|

The Instrumented Indentation Study of HVOF-Sprayed Hardmetal Coatings

Abstract: Elastic-plastic properties, namely, hardness and YoungÕs modulus, of four HVOF-sprayed hardmetal coatings were measured by instrumented indentation using Oliver-Pharr method Nanoindenter XP MTS with a continuous stiffness measurement (CSM) module. The results show that with sufficient number of CSM measurements, one can distinguish between indents made in the hard particles and indents made in the binder material. This can be accomplished by analyzing the plots of hardness and YoungÕs modulus versus load (or v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 47 publications
5
17
0
Order By: Relevance
“…The elastic moduli E c , which were computed following this methodology, exhibit the same trend reported in Table 2, when the computation is carried out employing equation (13), although their magnitude is somewhat less.…”
Section: Yield Strength Of Coatingsmentioning
confidence: 57%
See 2 more Smart Citations
“…The elastic moduli E c , which were computed following this methodology, exhibit the same trend reported in Table 2, when the computation is carried out employing equation (13), although their magnitude is somewhat less.…”
Section: Yield Strength Of Coatingsmentioning
confidence: 57%
“…The ISE determined for contact depths of ,1?5 mm in the coatings is in agreement with the results reported previously by several authors in different materials deposited by HVOF thermal spraying. 12,13,16,32,33 La Barbera-Sosa et al 16,32 and Santana et al 12 have reported the occurrence of a marked ISE in both Ni and WC based coatings for indentation loads less than y2 N, equivalent to penetration depths in the range of approximately 1-2 mm. Such an effect is associated with the microstructure involved in the small indentation volume, as well as the occurrence of the coating microcracking.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…4. Authors [13] visualized dependence of microstructure, properties and wear rate of the cermet coatings containing metallic binder phase in Fig. 10.…”
Section: Wc-co Wc-nimocrfeco Co-mocrsimentioning
confidence: 99%
“…Values obtained helped the study of splat boundaries, pores, oxides and microcracks present in the coating composite. 25 Afrasiabi The available literature provides ample insights to the methods of mechanical characterisation of bulk materials, thin films and functionally graded materials in terms of hardness and elastic modulus. Very few actually studied plasma-sprayed alumina coatings to evaluate elasto-plastic responses through indentation.…”
Section: Introductionmentioning
confidence: 99%